EP586 Robotic surgery and perioperative morbidity in very elderly women (≥75 years old) with type 2 endometrial cancer. (1st November 2019) - Myriokefalitaki, E; Winter-Roach, B; Slade, R; Smith, M
Abstract : Introduction/Background: To investigate the feasibility, safety, and short-term outcomes for very elderly patients, age ≥75 years undergoing robotic surgery for intermediate and high risk endometrial cancer. Methodology: Retrospective cohort study of all patients ≥75 years old that underwent robotic surgery for the treatment of endometrial cancer in our centre between July 2014 and April 2019. Results: 84 patients identified with a mean age of 79 (75–91) years old. All of them underwent total hysterectomy + bilateral salpingo-oophorectomy and 70 of them underwent also pelvic Lymphadenectomy with a mean count of 17.0. 72% of them had cardiovascular disease and 28% of them chronic obstructive pulmonary disease. 50% of them had previous abdominal surgery and 17% of them had a performance status (ECOG) ≥2. Compared to the younger group of our patients (mean age 63.4, range 32–74 years old), mean length hospital stay was slightly longer 2.7 days vs 2.1 (p<0.05). There were 8.3% grade I–II (Clavien-Dindo) post-operative complications vs 7.4% (p>0.05) and 4.7% grade III–IV vs 3.2% (p<0.05). The difference was observed to complications related to chest infection and postoperative arrhythmia (AF). There were no deaths. Conclusion: Robotic surgery is feasible and safe in very elderly women with type 2 endometrial cancer. We observed a longer hospital length of stay and greater likelihood of postoperative arrhythmia in comparison to patients ≤75 years old. Patients should not be considered too old for robotic surgery. Pre and perioperative care should take into account their comorbidities and tailored accordingly. Disclosure: The Christie is an accredited training centre for robotic surgery in Gynaecological oncology.